2021
DOI: 10.3390/horticulturae7100393
|View full text |Cite
|
Sign up to set email alerts
|

Morpho-Anatomical and Biochemical Characterization of Embryogenic and Degenerative Embryogenic Calli of Phoenix dactylifera L.

Abstract: The study of morpho-anatomical aspects, metabolic changes of proteins, antioxidant substances, as well as phenolic compounds in embryogenic callus (EC) and degenerative embryogenic callus (DEC) was the aim of the present investigation. Ability to form somatic embryos (SEs) was associated with the softness of the EC, which exhibited a white or creamy color and was composed of isodiametric cells containing dense cytoplasm, conspicuous nuclei and minimal vacuoles with observed mitotic activity. Furthermore, prote… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
2

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(10 citation statements)
references
References 63 publications
1
9
0
Order By: Relevance
“…Also, endogenous antioxidant levels were discovered to be higher in proliferative cells than in developing cells [ 6 , 9 , 20 ]. Furthermore, Zein El Din et al [ 5 ] observed that the reduced forms of ASC and GSH were identified in higher amounts in EC than in the degenerative embryogenic callus (DEC) of date palm cv. Barhee grown in vitro.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Also, endogenous antioxidant levels were discovered to be higher in proliferative cells than in developing cells [ 6 , 9 , 20 ]. Furthermore, Zein El Din et al [ 5 ] observed that the reduced forms of ASC and GSH were identified in higher amounts in EC than in the degenerative embryogenic callus (DEC) of date palm cv. Barhee grown in vitro.…”
Section: Discussionmentioning
confidence: 99%
“…Protein content within EC cells increased when EC was placed in antioxidants containing media ( Figure 2 A). The importance of protein deposition in EC can be explained by its correlation with higher cell division, and metabolic activities in date palm embryogenic callus [ 5 ] and in nodular cluster cultures of Vriesea reitzii [ 30 ]. Moreover, it has been discovered that proteins were stored in the nucleus of EC at a high level [ 31 ].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The marketability of fruits and vegetables depends on the quality attributes such as physical appearance, firmness, and shelf life of commodities which are important from the consumer point of view (Abdallah et al, 2021). At the time of purchasing, consumers judge the quality of commodities based on the appearance and firmness of fruits and vegetables (Rezk et al, 2019;Dawi et al, 2021;Zein et al, 2021). Storage performance and quality of fruits depend on maturity stages.…”
Section: Introductionmentioning
confidence: 99%